Teaching practicum supervisors' identity and student assessment on the practicum: An assorted mind-set? - Namubiru-Ssentamu, Proscovia (Africa Education Review, 2010)
The study examined the influence of teaching practicum supervisors’ identity on student assessment during the practicum. Identity was based on supervisors’ teaching experience and subject background. Using a confirmatory research design with qualitative and quantitative methods, data was drawn from 150 assessment forms on lessons observed by 15 supervisors’ during practicum besides follow-up interviews. Findings show that there is no relationship between supervisors’ identity and assessment of students’ knowledge of subject content. However, a significant relationship is suggested between supervisors’ identity and rating of students’ teaching plans, communication, use of instructional materials, classroom management, and evaluation of the teaching and learning process. Emphasis during assessment was placed on context-dependent rather than contextindependent variables of the observed lessons. Context-dependent aspects are perceived differently by supervisors because they require students to reconstruct acquired knowledge to solve diverse teaching-related challenges. The assessment form completed by supervisors during lesson observation is a platform for discourse between the objective and subjective elements of assessment, whose outcome eventually determines students’
Keywords: Teacher education; teaching; teaching practicum supervisor; practicum